1993
DOI: 10.1002/hlca.19930760312
|View full text |Cite
|
Sign up to set email alerts
|

Assignment of 15N‐NMR resonances of vitamin B12 analogues by 2D‐[15N, 1H] long‐range correlation: Fully [15N]‐labelled Co‐β‐cyano‐5‐hydroxybenzimidazoylcobamide (factor III) and derivatives

Abstract: The "N-NMR spectra of vitamin B12 analogues obtained in fully "N-labelled form have been measured by direct and inverse (15N,lH) correlated spectroscopy. All resonances, except those of the NH, groups, have been assigned to individual N-atoms. The influences on 6(N) are analyzed and discussed which are caused by changing the B-face ligand from CN to H 2 0 or CH3 and by switching the a -face ligand from the base-on to the base-off state. An implication of the correct resonance assignment on biosynthetic pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1993
1993
2000
2000

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
(9 reference statements)
1
3
0
Order By: Relevance
“…All cobalt-coordinated N atoms were deshielded when the Coil ligand was changed from CN to methyl. Adding an electron-donating ligand such as a methyl group to the cobalt centre weakens the nitrogen-complexing cobalt bonds, including the Co-N bond of the nucleotide loop [19]. These data are consistent with the thermodynamic 'trans effect' which was demonstrated also by the rapid equilibration of CH3-cobalamin with nucleotide-free cobinamides in anaerobic solutions at room temperature [20].…”
Section: Chemical Properties Of Corrinoidssupporting
confidence: 77%
See 1 more Smart Citation
“…All cobalt-coordinated N atoms were deshielded when the Coil ligand was changed from CN to methyl. Adding an electron-donating ligand such as a methyl group to the cobalt centre weakens the nitrogen-complexing cobalt bonds, including the Co-N bond of the nucleotide loop [19]. These data are consistent with the thermodynamic 'trans effect' which was demonstrated also by the rapid equilibration of CH3-cobalamin with nucleotide-free cobinamides in anaerobic solutions at room temperature [20].…”
Section: Chemical Properties Of Corrinoidssupporting
confidence: 77%
“…The influence of the CH3, H20 or CN Co/3 ligands, and the base-on/base-off configuration of the Coo ligand on the electronic corrinoid structure were investigated also by using 15N-NMR spectroscopy [19]. The NMR technique was applied to the completely ~SN-labeled vitamin Bl2 analogue, factor III, i.d.…”
Section: Chemical Properties Of Corrinoidsmentioning
confidence: 99%
“…Some of these data are illustrated in Figures and , respectively. From the former it appears that not all nitrogen sites are observable in the 15 N CPMAS experiments: on comparing the polymorphs results with the assigned 15 N NMR spectra available for the vitamin in solution, , it would seem that only the six amide sites and the benzimidazol site NB 1 contribute to the solid line shape. The absence of the remaining five nitrogens even after assaying a variety of contact times (1−15 ms long) suggests a strong residual coupling between these “missing” sites and the cobalt atom to which they are all directly bonded; indeed, a recent cobaloxime−( 15 N)pyridine solid-state NMR study has shown that such couplings can exceed 500 Hz, and for our natural abundance cobalamins this could easily broaden signals beyond the limit of detection.…”
Section: Resultsmentioning
confidence: 99%
“…Spectroscopic methods of analysis have also been extensively applied to shed light on the relation between cobalamins reactivity and their structural and electronic nature. Particularly important has been the advent of modern pulsed NMR methods, which stimulated investigations on the solution-phase electronic and geometric nature of the molecules as revealed by the 13 C chemical shifts of various sites and by specific J -coupling constants or Overhauser enhancements between 1 H NMR resonances. , Central to the success of these studies was the introduction of multidimensional NMR, which enabled full and unambiguous resonance assignments for these otherwise overtly complex chemical compounds. It has also been recently shown that NMR observations on the 59 Co isotope itself, particularly in the solid state, could constitute yet another source of information regarding the electronic structure surrounding the metal. , Furthermore, such solid-phase measurements could help bridge the gap between the structural information available from diffraction studies on crystals and the combined structure/electronic insight available from solution-state chemical shift or coupling analyses.…”
Section: Introductionmentioning
confidence: 99%